Pemanfaatan Pengalaman Sejarawan untuk Meningkatkan Keterampilan Peserta Didik dalam Penelitian Sejarah - Labibatussolihah, Labibatussolihah (Prodi. Pendidikan Sejarah FPIPS UPI dan APPS (Asosiasi peneliti dan Pendidik Sejarah), 2020)
In this era when technological advances make students vulnerable to unverified information, hoax, history learning has an important role in stimulating their criticism and literacy skills. Students understanding in the historical method which is consists of heuristics, criticism, interpretation, and art of historical writing as an effective working tool should be pursued one of them by obtaining such knowledge from historian’s experience presented in the learning process. This study uses the classroom action research method with Elliot's design to answer the problem of how to improve students' abilities in historical research through the use of historian's experience? From this study it can be concluded 1) there is increase in historical research skills after the students get material historian experience; 2) it also increase students' criticism in choosing sources of reference; 3) history learning becomes more interesting and challenging for students.Keyword: Historical method, history learning, historical research, historian, classroom action research